2016
DOI: 10.1016/j.neulet.2016.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cell surface expression of chloride transporters during epileptogenesis

Abstract: The process is commonly known as epileptogenesis refers to the cascade of molecular and cellular changes that transform the brain to make it hyperexcitable and capable of generate recurrent spontaneous seizures. Unfortunately, our understanding of the molecular changes that affect the brain during epileptogenesis remains incomplete. Recent evidence suggests that dysfunction of cation-chloride transporters (CCCs) might be one of the factors that contribute to the deficits in inhibitory neurotransmission observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Post Traumatic Epilepsy: Richard Miles and colleagues demonstrated that GABA A receptor activation could be excitatory in human brain tissue resected for control of medically intractable epilepsy (Cohen et al ., 2002). However, the pathomechanism has never been elucidated (Huberfeld et al ., 2007; González, 2016; Karlócai et al ., 2016). Gliosis is the most common finding in medically intractable epilepsy (Thom, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Post Traumatic Epilepsy: Richard Miles and colleagues demonstrated that GABA A receptor activation could be excitatory in human brain tissue resected for control of medically intractable epilepsy (Cohen et al ., 2002). However, the pathomechanism has never been elucidated (Huberfeld et al ., 2007; González, 2016; Karlócai et al ., 2016). Gliosis is the most common finding in medically intractable epilepsy (Thom, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A single chemoconvulsant-induced seizure episode during P5-7 may result in an upregulation of KCC2 (Khirug et al, 2010) in a non-SE model. This is in contrast to downregulation of KCC2 seen in an adult SE model (Gonzalez, 2016). This study characterized pentylenetetrazole (PTZ)-induced neonatal seizures in CD-1 pups at P7 to determine their response to PB and BTN, to investigate the role of the TrkB pathway and associated KCC2 functional modulation.…”
Section: Introductionmentioning
confidence: 97%
“…KCC2 down-regulation weakens KCC2 function and GABA inhibition, in turn, accelerates and facilitates seizure induction (Munakata et al, 2007 ; Eftekhari et al, 2014 ; Hübner, 2014 ; Kahle et al, 2014 , 2016 ; Karlócai et al, 2016 ; Chen et al, 2017 ). However, the mechanism of seizure-induced KCC2 down-regulation remains inconclusive despite the abundance of studies on seizure development (Li et al, 2008 ; Puskarjov et al, 2015 ; González, 2016 ).…”
Section: Introductionmentioning
confidence: 99%